Penetapan Metode Ekstraksi Kalium Terbaik untuk Tanaman Tomat (Solanum lycopersicum L.) pada Tanah Andisol - Gunawan, Endang; Susila, Anas D.; Sutandi, Atang; Santosa, Edi (Jurnal Hortikultura Indonesia, 2019)
Determination of recommendations for potassium (K) based on soil tests for tomato in Andisol is rarely studied in Indonesia. This experiment was started by making of K soil status in IPB Research Station Pasirsarongge Ciputri Cianjur and followed by correlation test in PKHT IPB greenhouse Tajur Bogor West Java, from Desember 2015 to May 2016. The objective of the experiment was to select the best extraction method of K for tomato on Andisol soil. The experiment used single location approach with randomized block design. The treatmens is soil K status by application of K2SO4 solution with five rate of K : 0, ¼,X, ½X, ¾X, and X. X was K rate of 413.4 kg K ha-1were applied to achieve maximum K concentration in the soil and incubated for 4 months to obtain different K nutrient status. Analysis of soil K using five extraction methods: Bray 1, HCl 25%, Morgan Wolf, Mechlich and NH4OAc. The results showed the differences in response of plant height and biomass dry weight to nutrient status of Andisols K. Quadratic response was shown in plant height at 6 and 7 weeks after planting and biomass dry weight. The best K extraction method was NH4OAc with correlation coefficient (r) of 0.75. Key words: biomass, extraction method, K status, K2SO4, NH4Oac